2016
DOI: 10.1073/pnas.1512600113
|View full text |Cite
|
Sign up to set email alerts
|

Thy1+IL-7+lymphatic endothelial cells in iBALT provide a survival niche for memory T-helper cells in allergic airway inflammation

Abstract: Memory CD4 + T helper (Th) cells are central to long-term protection against pathogens, but they can also be pathogenic and drive chronic inflammatory disorders. How these pathogenic memory Th cells are maintained, particularly at sites of local inflammation, remains unclear. We found that ectopic lymphoid-like structures called inducible bronchus-associated lymphoid tissue (iBALT) are formed during chronic allergic inflammation in the lung, and that memory-type pathogenic Th2 (Tpath2) cells capable of driving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
100
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(110 citation statements)
references
References 64 publications
3
100
0
Order By: Relevance
“…However, more recent data indicates that lymphatics are more than a transportation system and lymphatic endothelial cells can recruit and activate inflammatory cells (30, 50). Lymphatic endothelial cells from bronchus-associated lymphoid tissue were shown to be Thy1 + IL-7 + IL-33 + and these cells were critical in supporting pathogenic Th2 cells during chronic allergen inflammation in human and mice (51). Results suggest that pathogenic lymphatic endothelial cells promote maintenance of T-cells at the local inflammatory sites within airways.…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent data indicates that lymphatics are more than a transportation system and lymphatic endothelial cells can recruit and activate inflammatory cells (30, 50). Lymphatic endothelial cells from bronchus-associated lymphoid tissue were shown to be Thy1 + IL-7 + IL-33 + and these cells were critical in supporting pathogenic Th2 cells during chronic allergen inflammation in human and mice (51). Results suggest that pathogenic lymphatic endothelial cells promote maintenance of T-cells at the local inflammatory sites within airways.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings demonstrated that the formation of inducible bronchus‐associated lymphoid tissue within the lung containing a large number of memory Th2 cells play a very important role during chronic allergic inflammation. The maintenance of memory Th2 cells within these tertiary lymphoid tissues is sustained by Thy1 + IL‐7‐producing lymphatic endothelial cells via mechanisms depending on the production of IL‐33 and CCL21 and CCL19 . The accumulation of effector cell‐derived mediators and the activation of memory allergen‐specific Th2 cells by antigen‐presenting cells (APC) (DCs and B cells) through mechanisms depending on IgE‐facilitated allergen presentation are key factors for the initiation and maintenance of late‐phase reactions.…”
Section: Immunologic Mechanisms Underlying Allergic Diseasesmentioning
confidence: 99%
“…Yet another key function of lymphatic endothelial cells in lymph nodes, and likely in nonlymphoid tissue, is the production of cytokines, which may be coordinated with the expression of molecules like LYVE-1 (66) and TLR-4, which is highly expressed by lymphatic endothelial cells and macrophages, but not DCs, as commonly thought (112, 115). With respect to cytokine production, lymphatic endothelial cells are the largest producer of IL-7 to maintain T cell homeostasis in lymph nodes (116118) and to sustain inflammation-induced lymphoid follicles in the context of disease (119). They also produce many other cytokines.…”
Section: Structure and Properties Of The Lymphatic Systemmentioning
confidence: 99%